2022
DOI: 10.1183/23120541.00056-2022
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function test and computed tomography features during follow-up after SARS, MERS and COVID-19: a systematic review and meta-analysis

Abstract: BackgroundThe COVID-19 pandemic follows SARS and MERS coronavirus epidemics. Some survivors of COVID-19 infection experience persistent respiratory symptoms, yet their cause and natural history remains unclear. Follow-up after SARS and MERS may provide a model for predicting the long-term pulmonary consequences of COVID-19.MethodsThis systematic review and meta-analysis aims to describe and compare the longitudinal pulmonary function test (PFT) and computed tomography (CT) features of patients recovering from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 133 publications
3
13
0
3
Order By: Relevance
“…Our results are in line with the first meta-analysis comparing lung function and radiological patterns over time after infection with SARS-CoV-2, severe acute respiratory syndrome virus, and Middle East respiratory syndrome virus [17]. Other studies showed that at 3 months, 42% of patients that had not required mechanical ventilation [18] and 82% of those that had COVID-19-related ARDS [19] displayed decreased DLCO.…”
Section: Discussionsupporting
confidence: 89%
“…Our results are in line with the first meta-analysis comparing lung function and radiological patterns over time after infection with SARS-CoV-2, severe acute respiratory syndrome virus, and Middle East respiratory syndrome virus [17]. Other studies showed that at 3 months, 42% of patients that had not required mechanical ventilation [18] and 82% of those that had COVID-19-related ARDS [19] displayed decreased DLCO.…”
Section: Discussionsupporting
confidence: 89%
“…5,7,8 Changes in pulmonary function are similar to those observed following other viral infections including SARS and MERS. 15 Even when excluding studies with less than 100 patients and those in specialist populations, variability in estimated prevalence between studies remained high, particularly in the non-hospitalised cohort. In addition to varying study designs, different follow-up measurement tools and a wide range of follow-up durations, observed heterogeneity between studies may be explained by the lack of standardised data collection tools, particularly in studies of non-hospitalised populations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, experience with patients suffering from persistent dyspnea after SARS-CoV-2 infection often shows no impairment in lung function and computed tomography [ 5 ]. Because of the limited experience with EIT in spontaneously breathing patients with post-COVID syndrome, it would be desirable to combine EIT with pulmonary function tests (PFT) [ 20 ], which are the gold standard, and cardiopulmonary exercise testing [ 21 ] on the same day.…”
Section: Discussionmentioning
confidence: 99%